2011
DOI: 10.1007/s00425-010-1339-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow from herbicide-tolerant GM rice and the heterosis of GM rice-weed F2 progeny

Abstract: Gene flow from genetically modified (GM) crops to non-GM cultivars or weedy relatives may lead to the development of more aggressive weeds. We quantified the amount of gene flow from herbicide-tolerant GM rice (Protox GM, derived from the cultivar Dongjin) to three cultivars (Dongjin, Aranghyangchal and Hwaseong) and a weedy rice line. Gene flow frequency generally decreased with increasing distance from the pollen donor. At the shortest distance (0.5 m), we observed a maximum frequency (0.039%) of gene flow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Rice is a self‐compatible autogamous species that can lead to pollen‐mediated outcrosses if short cultivation distances between individuals are applied between cultivars or subspecies, or when their flowering periods overlap. Pollen‐mediated gene flow from GM to conventional rice cultivars was already reported, with percentages ranging from <0.2% between immediate neighbouring or mixed plants in a plot and up to <1% for more distant plots (Chun et al ., ; Jia et al ., ; Messeguer et al ., , ; Rong et al ., , ; Serrat et al ., ). Additionally, by the use of different experimental designs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Rice is a self‐compatible autogamous species that can lead to pollen‐mediated outcrosses if short cultivation distances between individuals are applied between cultivars or subspecies, or when their flowering periods overlap. Pollen‐mediated gene flow from GM to conventional rice cultivars was already reported, with percentages ranging from <0.2% between immediate neighbouring or mixed plants in a plot and up to <1% for more distant plots (Chun et al ., ; Jia et al ., ; Messeguer et al ., , ; Rong et al ., , ; Serrat et al ., ). Additionally, by the use of different experimental designs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment results have shown that the frequency of transgene flow to red rice is similar to that between cultivated rice, because they are primarily self‐pollinated (e.g. Chen et al ., ; Chun et al ., ; Messeguer et al ., ; Olguin et al ., ; Song et al ., b; Song et al ., ). Gealy et al .…”
Section: Gene Flow Patterns In Rice and Its Wild Relativesmentioning
confidence: 99%
“…Experiment results have shown that the frequency of transgene flow to red rice is similar to that between cultivated rice, because they are primarily self-pollinated (e.g. Chen et al, 2004;Chun et al, 2011;Messeguer et al, 2004;Olguin et al, 2009;Song et al, 2002b;Song et al, 2009). Gealy et al (2003) reviewed more than ten published papers on the rates of gene flow from cultivated rice to weedy rice and noted that typical rates of cropweed hybridization were in the range of 0%-1.00%.…”
Section: Transgene Flow To Weedy Rice and Weedsmentioning
confidence: 99%
“…As shown in Table 1, molecular markers (e.g. microsatellites) are also used to quantify of crop-to-weed and crop-to-wild gene flow (Messeguer et al 2004;Olguin et al 2009;Chun et al 2011;Jia et al 2014). Gene flow results collected from these experimental studies are the first step for assessing the impact of cropto-weed and crop-to-wild transgene flow in rice.…”
Section: Gene Flow: From Cultivated To Weedy Ricementioning
confidence: 99%